Two new supramolecular assemblies obtained by reaction between saccharin and long-chain diamines - Castellano, Eduardo Ernesto (2009)
The crystal structures of heptamethylenediammonium bis(saccharinate) monohydrate, [H3N-(CH2)7-NH3J(sac) 2-H2O(1) and octamethylenediammonium bis(saccharinate) hemihydrate, [H3N-(CH2)8-NH3J(sac) 2-0.5H2O(2), were determined by single-crystal X-ray diffraction methods. Compound 1 crystallizes in the triclinic space group PI with 2 molecules per unit cell, and 2 in the mono-clinic space group P2 1/a with Z = 4. The saccharinate moiety is planar in both compounds presenting bonding characteristics comparable to those found in other saccharinate salts. The ionic crystals are fürther stabilized by an extensive H-bonding network, which links the anions and cations into an infinite three-dimensional supramolecular assembly. The FTIR spectra of the adducts are briefly discussed in comparison with those of the constituent molecules.